Criador, criação e criatura : os intervalos de silêncio enquanto bastidores para o nascer do poema - Neu, Daniela Damaris (2013)
This study presents a discussion about the creative process in the context of poetry, a field in which we must consider not only the poem, the act of writing, but what happens, and especially what precedes it. We believe there is an element that is essential in this process: the silence. There is silence before the poem, its primordial to the existence of the poem. And there is silence after the poem is written and after it is read. Several important theorists position themselves in relation to the creation of poetry, many of them citing just silence, and lend their theories to strengthen our arguments. Among them are Blanchot, Bachelard, Trevisan, Pavese, Orlandi, Pound, Paz, Lezama Lima, Borges, Barthes, Valéry, Zambrano, among others. Joins them no more a poet who also makes theory, but a poet, Élvio Vargas, who brings the poetry itself the possibility to identify traits that may say that there is something beyond the poem, and that this is something beyond the raw material for the poetic word. This, in turn, arises in the intervals between one and another silence.